Blue birds - Rose, Caroline Starr (G. P. Putnam's Sons, an imprint of Penguin Group (USA), 2015)
"As tensions rise between the English settlers and the Native peoples on Roanoke Island, twelve-year-old Alis forms an impossible friendship with a native girl named Kimi"--